Bilateral Pulmonary Emboli Secondary to Indwelling Hemodialysis Reliable Outflow Catheter. (May 2013) - Coan, Kathryn E.; O'Donnell, Mark E.; Fankhauser, Grant T.; Bodnar, Zachary; Chandrasekaran, Krishnaswamy; Stone, William M.
We present a 33-year-old dialysis-dependent female who presented with new onset split second heart sound. Following a failed left upper extremity dialysis fistula, a right upper extremity hemodialysis reliable outflow (HeRO) graft was performed in 2011. Her subsequent cadaveric renal transplant had delayed function necessitating concurrent use of hemodialysis. However, as renal function improved, hemodialysis was discontinued. Two weeks following transplantation, the HeRO graft occluded. Subsequent clinical and radiological assessment confirmed widespread pulmonary emboli. Following cessation of hemodialysis and subsequent HeRO graft occlusion, removal was deemed appropriate to reduce further thromboembolic phenomenon. Right atrial thrombi are complications associated with central venous catheters. However, their actual incidence varies significantly. Right heart thromboemboli are associated with a 4% to 6% pulmonary embolism rate. Katzman et al assessed 38 patients who underwent HeRO graft and reported 1 (2.6%) patient with right atrial emboli and likely pulmonary embolism. Although thrombotic complications remain rare, consideration of graft removal should always be evaluated particularly in the absence of an alternative thrombotic source.